Mechanical properties of 3D printed polymeric cellular materials with triply periodic minimal surface architectures. (15th May 2017) - Abueidda, Diab W.; Bakir, Mete; Abu Al-Rub, Rashid K.; Bergström, Jörgen S.; Sobh, Nahil A.; Jasiuk, Iwona
Abstract: In this paper, three types of triply periodic minimal surfaces (TPMS) are utilized to create novel polymeric cellular materials (CM). The TPMS architectures considered are Schwarz Primitive, Schoen IWP, and Neovius. This work investigates experimentally and computationally mechanical properties of these three TPMS-CMs. 3D printing is used to fabricate these polymeric cellular materials and their base material. Their properties are tested to provide inputs and serve as validation for finite element modeling. Two finite deformation elastic/hyperelastic-viscoplastic constitutive models calibrated based on the mechanical response of the base material are used in the computational study of the TPMS-CMs. It is shown that the specimen size of the TPMS-CMs affect their mechanical properties. Moreover, the finite element results agree with the results obtained experimentally. The Neovius-CM and IWP-CM have a similar mechanical response, and it is found that they have higher stiffness and strength than the Primitive-CM. Graphical abstract: Highlights: Triply periodic minimal surfaces (TPMS) are utilized to create new cellular materials (CMs). The modulus and strength of three types of TPMS-CMs are found experimentally and computationally. Post-yielding behavior of the three TPMS-CMs is reported and discussed. Failure (buckling vs. yielding) maps are reported.